Formal Asymmetric (4+1) Annulation Reaction between Sulfur Ylides and 1, 3‐Dienes. Issue 37 (31st July 2015) - Rousseau, Olivier; Delaunay, Thierry; Dequirez, Geoffroy; Trieu‐Van, Tran; Robeyns, Koen; Robiette, Raphaël
Abstract A highly enantioselective synthesis of functionalized cyclopentanoids by a formal asymmetric (4+1) annulation strategy was developed. The methodology consists of a stereoselective cyclopropanation reaction between chiral sulfur ylides and 1, 3‐dienes followed by a, in situ, stereospecific MgI2‐catalyzed rearrangement of vinylcyclopropanes. This method is distinguished by a remarkable compatibility with functional groups and a high stereocontrol.